2007
DOI: 10.21608/fjard.2007.197557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substituting Yellow Corn by by-Products of Some Medicinal and Aromatic Plants With or Without Enzyme Supplementation on Growing Japanese Quail Performance

Abstract: Chemical analyses were performed in the laboratories of the same Department.The experiment was conducted during the period from March to April 2005. The effect of substituting yellow corn by some by-products of medicinal and aromatic plants with or without enzyme supplementation was studied on growing Japanese quail performance. Fourteen dietary treatments were designed to study the effects of substituting yellow corn by some by-products of medicinal and aromatic plants with or without enzyme supplementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Supplementation of the diets with fresh parsley leaf can signi cantly increase antioxidant capacity 44 . 45 have demonstrated that it is possible to replace 16% of yellow corn with aromatic plants (parsley, mint etc.) in quail diets.…”
Section: Carcass Characteristics and Organs Weightmentioning
confidence: 99%
“…Supplementation of the diets with fresh parsley leaf can signi cantly increase antioxidant capacity 44 . 45 have demonstrated that it is possible to replace 16% of yellow corn with aromatic plants (parsley, mint etc.) in quail diets.…”
Section: Carcass Characteristics and Organs Weightmentioning
confidence: 99%
“…These variations may be attributed to the effects of heat on oil, microbial and biochemical processes during processing, as well as the increased activity of lipases during soaking. These variations may be attributed to the effects of heat on oil, microbial and biochemical processes during processing, as well as the increased activity of lipases during soaking In a related experiment Ragab et al (2002) and Banja et al (2016) attributed decreased lipid content of soya bean meal to biochemical reaction and dissociation of lipid complexes. Dissimilar assertion has been made by Agume et al (2017), who reported decreased lipid content of soya bean meal after processing including soaking.…”
Section: Soleamentioning
confidence: 99%